Enrico Fermi The Obedient Genius - Bruzzaniti, Giuseppe (Springer Biographies,, 2016)
This biography explores the life and career of the Italian physicist Enrico Fermi, which is also the story of thirty years that transformed physics and forever changed our understanding of matter and the universe: nuclear physics and elementary particle physics were born, nuclear fission was discovered, the Manhattan Project was developed, the atomic bombs were dropped, and the era of "big science" began. It would be impossible to capture the full essence of this revolutionary period without first understanding Fermi, without whom it would not have been possible. Enrico Fermi: The Obedient Genius attempts to shed light on all aspects of Fermi's life - his work, motivation, influences, achievements, and personal thoughts - beginning with the publication of his first paper in 1921 through his death in 1954. During this time, Fermi demonstrated that he was indeed following in the footsteps of Galileo, excelling in his work both theoretically and experimentally by deepening our understanding of the Pauli exclusion principle, winning the Nobel Prize for his discovery of the fundamental properties of slow neutrons, developing the theory of beta decay, building the first nuclear reactor, and playing a central role in the development of the atomic bomb. Interwoven with this fascinating story, the book details the major developments in physics and provides the necessary background material to fully appreciate the dramatic changes that were taking place. Also included are appendices that provide a timeline of Fermi's life, several primary source documents from the period, and an extensive bibliography. This book will enlighten anyone interested in Fermi's work or the scientific events that led to the physics revolution of the first half of the twentieth century. .